Peer-based Retention Of people who Use Drugs in Rural Research (PROUD-R2): a multisite, randomised, 12-month trial to compare efficacy of standard versus peer-based approaches to retain rural people who use drugs in research - Morgan Brown; Miriam R Elman; Jodi Lapidus; April M Young; Kathryn E Lancaster; Sarann Bielavitz; Ryan R Cook; Gillian Leichtling; Edward Freeman; Angela T Estadt; Rhonda Alexander; Caiti Barrie; et al. (BMJ Open)
Introduction Rural communities bear a disproportionate share of the opioid and methamphetamine use disorder epidemics. Yet, rural people who use drugs (PWUD) are rarely included in trials testing new drug use prevention and treatment strategies. Numerous barriers impede rural PWUD trial engagement and advancing research methods to better retain rural PWUD in clinical trials is needed. This paper describes the Peer-based Retention Of people who Use Drugs in Rural Research (PROUD-R2) study protocol to test the effectiveness of a peer-driven intervention to improve study retention among rural PWUD.Methods and analysis The PROUD-R2 study is being implemented in 21 rural counties in three states (Kentucky, Ohio and Oregon). People who are 18 years or older, reside in the study area and either used opioids or injected any drug to get high in the past 30 days are eligible for study inclusion. Participants are allocated in a 1:1 ratio to two arms, stratified by site to assure balance at each geographical location. The trial compares the effectiveness of two retention strategies. Participants randomised to the control arm provide detailed contact information and receive standard retention outreach by study staff (ie, contacts for locator information updates, appointment reminders). Participants randomised to the intervention arm are asked to recruit a ‘study buddy’ in addition to receiving standard retention outreach. Study buddies are invited to participate in a video training and instructed to remind their intervention participant of follow-up appointments and encourage retention. Assessments are completed by intervention, control and study buddy participants at 6 and 12 months after enrolment.Ethics and dissemination The protocol was approved by a central Institutional Review Board (University of Utah). Results of the study will be disseminated in academic conferences and peer-reviewed journals, online and print media, and in meetings with community stakeholders.Trial registration number NCT03885024